Pengukuran Rate Kualitas Villa-Vila Daerah Puncak Bogor dengan Logika Fuzzy Metode Tsukamoto - Bramantara Yudha (Teknik Informatika Universitas Pamulang, 2021)
The growth of the villa rental business in the Puncak Bogor area is increasing and resulting in more stringent competition in this industry. Industrial entrepreneurs try to offer many advantages of facilities and services for customers. The previous quality measurement used a questionnaire method addressed to customers. This quality measurement method results are used for evaluation as a standard for the quality level of the villas. A requirement to get a good rating is the service of the villa in standard calculations using this method. The research was conducted to produce accurate quality calculations using fuzzy implementation using the Tsukamoto method. The working record of this method represents a monotonous fuzzy set on the membership function. Research on the analysis of the calculation of rental prices for villas in the Puncak area of Bogor with the fuzzy logic of the Tsukamoto method produces inference values for all rules according to the standard value calculation for the variable value of Villa quality standards. The value is based on the variable type of room, facilities and rental price.